Changes in epigenetic markers, DNMT1 and HDAC1/2, in the adult mouse hippocampus after cranial irradiation. (14th September 2017) - Kang, Sohi; Son, Yeonghoon; Lee, Sueun; Kim, Juhwan; Kim, Jong-Choon; Kim, Joong-Sun; Jung, Uhee; Kim, Sung-Ho; Yang, Miyoung; Moon, Changjong
Highlights: Epigenetic modification plays an important role during hippocampal memory processing. Cranial irradiation inhibited hippocampal epigenetic modification signals in mice. Decreased epigenetic modification signals may be involved in radiation-induced hippocampal dysfunctions. Abstract: Brain exposure to ionizing radiation can cause functional deficits in the hippocampus, including memory impairment. However, the specific molecular mechanisms underlying irradiation-induced cognitive impairments are largely unknown. Changes in DNA methyltransferases (DNMTs) and histone deacetylases (HDACs), which are involved in DNA methylation and histone remodeling, may be associated with behavioral changes in learning and memory. We assessed changes in the levels of enzymes associated with the epigenetic modification of gene expression, including DNMT1, HDAC1, HDAC2, Sirtuin 1 (SIRT1), and acetylated histone H3 (Ace-H3) in the mouse hippocampus 1 and 30 days after a single exposure to cranial irradiation (0 or 10 Gy). mRNA levels of HDAC1 were significantly downregulated 1 day after irradiation with 10 Gy, and those of DNMT1, HDAC1, and HDAC2 were significantly downregulated 30 days post-irradiation. Western blot analysis revealed significant decreases in DNMT1, HDAC1, and HDAC2 protein levels 1 and 30 days after irradiation with 10 Gy. Furthermore, protein levels of SIRT1 and Ace-H3 were significantly downregulated in the mouse hippocampus 1 and 30 days after cranial irradiation. Our findings suggest that the reduction in epigenetic gene expression is associated with hippocampal dysfunction in mice exposed to cranial irradiation.